Living cosmology : Christian responses to Journey of the universe - Tucker, Mary Evelyn (Ecology and justice., 2016)
Journey of the Universe is both a book, a film, and a conversation series by Mary Evelyn Tucker and Brian Swimme that offers a rich unfolding of "the universe story"--a moving narrative of cosmic evolution from the origins of the cosmos to the present. This volume explores the Christian responses to the Universe Story and its implications for the contemporary environmental crisis. Beginning with excerpts from recent statements by Pope Francis and the Ecumenical Patriarch Bartholomew, the book draws on the contributions of leading theologians, ethicists, scientists, and activists, including John Haught, Ilia Delio, Catherine Keller, Larry Rasmussen, and more than twenty-five others. (Publisher).